Wcześniejszy wpływ gotówki a rentowność kapitału własnego - Berent, Tomasz (The Impact of Earlier Cash Inflow on Return on Equity, 2008)
Based on a simple single-period model, the paper analyzes the impact of the earlier cash inflow on the return on equity. The increased volatility of rates of return is shown to result from: firstly, lowering the amount of equity employed and, secondly, from non-zero cost associated with earlier cash inflow. As such, the model can be used in further analysis of leverage (incl. financial leverage) and the methods of its measurement. Thanks to its generality, the model can be applied to various financial settings and used as a tool to analyze the impact of financial leverage, payment policy to/from suppliers/clients, etc. on the return on equity. The focus of the article is on the analysis of the volatility of rates of return itself rather than on the impact of this volatility on the asset pricing, the cost of capital, etc.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 50-61